The Effect of Growth Opportunity, Leverage, Firm Size on Hedging Decisions - Salsabela, Dania; Salih , Lea Berliana Jeni; Wardana, Muhammad Indra; Pandin, Maria Yovita R. (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
Risk management in investment portfolios focuses on hedging strategies and the use of derivative instruments. In the context of international trade and unpredictable market fluctuations, risk management becomes a crucial aspect in maintaining the stability and sustainability of investments. This study explains the various types of risks faced by investors, including market risk, interest rate risk, currency risk, and credit risk. Hedging strategies, which aim to reduce potential losses without sacrificing profit opportunities, are implemented through derivative instruments such as futures contracts, options, and swaps. Through quantitative analysis, this article provides insights into the effectiveness of using derivative instruments to protect portfolio value. These findings are expected to offer practical recommendations for companies and investors in managing risks and enhance understanding of the importance of hedging strategies in achieving optimal investment outcomes.